Unlocking Spiritual Growth: Implementing Tahfidh Program at Muhammadiyah Vocational School - Tamimi, Muhyiddin Tohir; Pratama, Ari Budi; Suharsiwi, Suharsiwi; Busahdiar, Busahdiar; Mubarok, Fauzi Al (Indonesian Journal of Islamic Education Studies (IJIES), 2024)
In vocational high schools focusing on academic science, students can learn religion through the tahfidz program. They can memorize the Al-Qur'an correctly with a systematic and focused program. This study aims to determine the implementation of the program and the improvement of students' memorization of the Al-Qur'an. This study uses a descriptive qualitative research method. The subjects of the study included the principal, deputy principal of ISMUBA, students, and religious teachers at Muhammadiyah 2 Palembang Vocational High School. Data were taken from the results of observations, interviews, and documentation. This study shows that the implementation of the tahfidz Al-Qur'an program is routinely carried out at the beginning of the first lesson after praying together and continued with a seven-minute lecture (kultum). This helps them memorize and understand the meaning of the contents of the verses of the Al-Qur'an. In addition, there is a follow-up in the form of mentoring, which is carried out after school hours are finished every week and is routinely mentored by ISMUBA teachers. Although this study is limited to one locus, it provides a theoretical contribution to learning the Al-Qur'an in vocational high schools in improving literacy and memorization of the Al-Qur'an through the tahfidh program.